Human biomonitoring of trace elements (Zn, Cu, Mn, Cd and As) level in a healthy urban population in Türkiye - Söylemez, Esma; Özçağlı, Eren; Göktaş, Eylem Funda; Kürekçi, Fulya; Omurtag, Gülden Zehra (Marmara University, 2023)
Human biomonitoring (HBM) studies are carried out to examine the effects of environmental pollutants on human health and to identify risks to public health, with the increasing awareness of environmental pollution around the world. The aim of our study is to determine the level of trace elements and to perform preliminary human biomonitoring of a healthy urban population in Türkiye. For this purpose, healthy individuals living in the same region and not known to have occupational or any other exposures were included in the study. Element levels from serum/blood of volunteers were determined. In this study, Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to analyze in order to determine the multi elements in a more precise way with an improved analytical quality of results. According to our study’s results, Mn and As (p<0.05) were found statistically significant with age. Smoking had an effect on Cd levels (p<0.01) and there were significant differences between males and females for only Zn (p[removed]
Keywords: Biomonitoring; Blood; ICP-MS; Serum; Trace Elements